Current Practices in Higher Education Institutes Pakistan and Gap Reduction between Industry and Academia: A Systematic Literature Review Approach - Junejo, Ikramuddin; Memon, Afzal Khan; Mohammad, Jan (Asian Journal of Contemporary Education, 2018)
This study investigates the current practices in higher education institutes and gap reduction between Industry and Academia. This study is based on literature review its objective is to review the current practices in higher education institutes and points out gaps. This reduced gap will balance demand and supply of graduates to industry and it has been practically observed that industry always complains for qualified graduates according to their expectations. Current practices in higher education institutes such as Internships, University based Incubation (UBI), Case study teaching and field trips. In this research paper systematic review approach of literature has been adopted for the conclusion of this study. All relevant studies published on this topic current practices and industry-academia from 1970 to 2014 was identified from database such as Google, Scopus and Web of science in various forms such as book, research articles, reports and websites. Based on results through literature review, current all studied practices can help to reduce gap between Industry and Academia. In previous studies researchers explored current studied practices individually. This research paper will help a triangle such as higher education institutes, industries and graduates for better mutual based relationship in future. This study can be extended in comparative analysis between developed and less developed countries.